Researching the Spatial Aspects of the Romani-Hungarian coexistence by the Means of Mental Mapping - Tünde Bogárdi; Melinda Molnár (DETUROPE)
In our study we shall analyse the spatial aspects of the Romani-Hungarian coexistence based on the field research results of the village seminar workshop organized by the Szent István University (Gödöllő). We present two different situations: one segregate analysis using Baks as an example, where we find a settlement considered as majority, and a Romani segregate; and provincial ghettoization using Átány as an example, where due to a previous site termination the Romani people dispersed over the whole village area. We conducted surveys in both settlements in order to find out the local residents’ opinion on the development of the value of the inhabited area. Our goal on the one hand is to present the method of ethnicity analysis by mental mapping in rural areas, and on the other in addition to offering methodological practices is to point out a few important takeaways of the spatiality of the Romani-Hungarian coexistence based on our actual experiences.